2014
DOI: 10.1210/en.2014-1334
|View full text |Cite
|
Sign up to set email alerts
|

The Sirtuin1 Activator SRT3025 Down-Regulates Sclerostin and Rescues Ovariectomy-Induced Bone Loss and Biomechanical Deterioration in Female Mice

Abstract: Estrogen deficiency leads to rapid bone loss and skeletal fragility. Sclerostin, encoded by the sost gene, and a product of the osteocyte, is a negative regulator of bone formation. Blocking sclerostin increases bone mass and strength in animals and humans. Sirtuin1 (Sirt1), a player in aging and metabolism, regulates bone mass and inhibits sost expression by deacetylating histone 3 at its promoter. We asked whether a Sirt1-activating compound could rescue ovariectomy (OVX)-induced bone loss and biomechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 39 publications
7
47
0
Order By: Relevance
“…Preliminary evidence gives reason to be optimistic: SIRT1 appears to promote commitment of MSCs towards the osteoblast lineage [4546, 4849] and repress differentiation of osteoclasts [43, 5051]. Indeed, recent studies with second and third generation SIRT1 agonists have shown even greater promise in preserving bone mass in mice [14, 52], raising hopes for a possible novel therapeutic for osteoporosis in the not so distant future.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence gives reason to be optimistic: SIRT1 appears to promote commitment of MSCs towards the osteoblast lineage [4546, 4849] and repress differentiation of osteoclasts [43, 5051]. Indeed, recent studies with second and third generation SIRT1 agonists have shown even greater promise in preserving bone mass in mice [14, 52], raising hopes for a possible novel therapeutic for osteoporosis in the not so distant future.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Artsi et al [44] found that ovariectomy in mice resulted in a marked decrease in skeletal Sirt1 expression accompanied by an increase in sclerostin. Interestingly, oral administration of SRT3025, a Sirt1 activator, reversed the deleterious skeletal effects of ovariectomy and also reduced bone sclerostin expression.…”
Section: Hormonal Regulation Of Sclerostinmentioning
confidence: 99%
“…The major impacts are antioxidative, antiinflammatory, cardioprotective, antiaging as well as anticancer and chemopreventive [13]. Sirtuin1 (Sirt1), an NAD + -dependent deacetylase and a key player in aging and metabolism, has been shown to regulate bone mass [14]. As a natural Sirt1 agonist, RES can upregulate the level of FOXOs and increase the activities of antioxidant enzymes in C2C12 mouse myoblasts cells and human monocytic THP-1 cells under oxidative stress conditions [15,16].…”
Section: Introductionmentioning
confidence: 99%